Denotasi dan Konotasi Tokoh Toyotomi Hideyoshi dalam Drama Taikouki (1987): Analisis Semiotika Roland Barthes - Taqdir, Taqdir; Fajrin, Muh.; Imelda, Imelda (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
This study examines the representation of Toyotomi Hideyoshi, initially known as Tokichiro, in the historical drama Taikouki (1987) directed by Kihachi Okamoto, using Roland Barthes' semiotic analysis. By analysing both denotative (literal) and connotative (deeper cultural and social) meanings, the research highlights Hideyoshi's multifaceted characterization as weak but determined, loyal, intelligent in strategy, charmingly flirtatious, humorous, and skilled in negotiation. These traits not only reflect his human side but also mirror key Japanese cultural values such as ganbaru (perseverance), wa (harmony), and leadership rooted in communication and diplomacy. The drama, produced during Japan's economic miracle in the 1980s, aligns Hideyoshi’s resilience and adaptability with societal ideals of the time, emphasizing the importance of collaboration and strategic thinking in overcoming challenges. Through Barthes’ semiotic approach, this study demonstrates how Taikouki functions as both a reconstruction of historical narratives and a reflection of contemporary cultural values. Ultimately, the drama reinforces Hideyoshi’s image as a visionary leader who achieved success through emotional intelligence, humor, and diplomacy, offering a nuanced portrayal that resonates with modern viewers while preserving his historical significance.